Health Aware Optimisation of the Energy Management of a Fuel Cell – Battery Hybrid Electric Vehicle - Skvor, Eva (My University, 2021)
The background of this thesis is the electric propulsion of heavy electric vehicles and the control problem of the optimal power split between a Lithium-ion battery and a proton-exchange membrane fuel cell system. Both the battery and the fuel cell degrade over time which impacts the resale value as well as the efficiency and life-time of a vehicle. The goal of this thesis is to expand the controller used at Volvo AB to include a cost for this degradation. Three previous works, Hu et al. (2019) [18], Feng et al. (2020) [13] and Wang et al. (2020) [38], are used as inspiration and to compare and evaluate the results. The overarching conclusion is that including degradation in the objective function is a sound option that decreases the total cost of ownership and increases the life time of the vehicle. Furthermore, spending some time on formulating good control models to accomplish this is defendable as they, according to this thesis, give better results than simple heuristic limitations on the use. Besides this, a sound theoretical foundation and a discussion on how the degradation should be modelled is carried out.
Keywords: fuel cells; battery; degradation; optimisation; heavy truck; propulsion